Maximum Aerobic Function: Clinical Relevance, Physiological Underpinnings, and Practical Application - Maffetone, Philip; Laursen, Paul B. (Frontiers in Physiology, 2020)
The earliest humans relied on large quantities of metabolic energy from the oxidation of fatty acids to develop larger brains and bodies, prevent and reduce disease risk, extend longevity, in addition to other benefits. This was enabled through the consumption of a high fat and low carbohydrate diet. Increased fat oxidation also supported daily bouts of prolonged, low-intensity, aerobic-based physical activity. Over the past 40-plus years, a clinical program has been developed to help people manage their lifestyles to promote increased fat oxidation as a means to improve various aspects of health and fitness that include reducing excess body fat, preventing disease, and optimizing human performance. This program is referred to as maximum aerobic function, and includes the practical application of a personalized exercise heart rate formula of low-to-moderate intensity associated with maximal fat oxidation, and without the need for laboratory evaluations. The relationship between exercise training at this heart rate and associated laboratory measures of maximal fat oxidation, health outcomes and athletic performance must be verified scientifically.